DAMPAK PERILAKU EKONOMI MASYARAKAT TERHADAP GANTI RUGI PENGADAAN TANAH TOL CIPALI UNTUK KEPENTINGAN UMUM - Sugianto Sugianto; Leliya Leliya (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2017)
AbstractThe public interest included the nation and the state interest and then the common interest, rights of land can be repealed with give proper compensation which is agree with law. One of them land acquisition for public interest such as Cipali Road Project as policy instruments was decided Sales Value of Taxable Object as basic calculation compesation land acquisition. The result of research is in the construction of Cipali Tollroad (Cirebon-Palimanan) Cirebon Regency because the construction of Cipali Tollroad is the public interest as â€œtwo sides of a coinâ€ certainly there are two problems or impact result from Cipali Tollroad that are: 1) Positive Impact: their excursions in the region of the exit of Cipali Tollroad (Cirebon, Kuningan, Majalengka) can be increase; attract investment industry sector in districts which be passed tollroad; distribution of goods is faster, so the price of goods is cheaper and inflation also is lower; the price of soil is increased significantly, can be absorb labor in the business sector;. 2) Negative Impact: makes people who sell/attempted in along the pantura stripe is suffer a financial loss and bankruptcy; the emergency of bad debts for bank customer in along the pantura stripe â€œin the outside of Cipali Tollroadâ€; society who be running a business in along the pantura stripe as is Cipali Tollroad moved into crowded place/area in the stripe of Tol Cipali (Cirebon-Palimanan). Keywords: Economic Behavior, Compensation, and Public Interest.Â AbstrakKepentingan umum, termasuk kepentingan bangsa dan negara serta kepentingan bersama, hak-hak atas tanah dapat dicabut dengan memberi ganti kerugian yang layak dan sesuai dengan tata cara yang diatur dalam undang-undang. Salah satunya pengadaan tanah untuk Kepentingan Umum yaitu Proyek jalan tol Cipali, sebagai instrumen kebijakan telah menetapkan NJOP (Nilai Jual Obyek Pajak)Â  sebagai dasar perhitungan kompensasi pengadaan tanah. Hasil Penelitian ini adalah dalam Pembangunan jalan Tol Cipali (Cirebon-Palimanan) Kabupaten Cirebon karena Pembangunan Jalan Tol Cipali merupakan Kepentingan Umum seperti â€œdua sisi mata uang â€œ tentunya ada dua problem atau dampak akibat tol Cipali yaitu; 1) Dampak Positif: Adanya kunjungan wisata diwilayah pintu keluar tol Cipali (Cirebon, Kuningan, Majalengka) dapat meningkat; Menarik investasi sektor industri dikabupaten - kabupaten yang terlalui jalan tol; Distribusi barang lebih lancar ,sehingga harga barang lebih murahÂ  dan inflasipun rendah; Harga tanah meningkat tajam, dapat menyerap tenaga kerja pada sektor sektor dunia usaha; 2) Dampak Negatif: Menjadikan masyarakat yang berjualan/usaha disepanjang jalan pantura rugi dan gulung tikar atau bangkrut; Munculnya kredit macet bagi nasabah Bank disepanjang jalur pantura â€œdiluar Tol Cipaliâ€; Masyarakat yang berusaha disepanjang jalur pantura dengan adanya Tol Cipali â€œPindah ke tempat/kawasan yang ramai di jalur Tol Cipali (Cirebon-Palimanan). Â Kata Kunci: Perilaku Ekonomi, Ganti Rugi, dan Kepentingan Umum.